A survey of the parallel performance and accuracy of Poisson solvers for electronic structure calculations. Issue 6 (19th November 2013) - García‐Risueño, Pablo; Alberdi‐Rodriguez, Joseba; Oliveira, Micael J. T.; Andrade, Xavier; Pippig, Michael; Muguerza, Javier; Arruabarrena, Agustin; Rubio, Angel
<x xml:space="preserve">Abstract</x> We present an analysis of different methods to calculate the classical electrostatic Hartree potential created by charge distributions. Our goal is to provide the reader with an estimation on the performance—in terms of both numerical complexity and accuracy—of popular Poisson solvers, and to give an intuitive idea on the way these solvers operate. Highly parallelizable routines have been implemented in a first‐principle simulation code (Octopus) to be used in our tests, so that reliable conclusions about the capability of methods to tackle large systems in cluster computing can be obtained from our work. © 2013 Wiley Periodicals, Inc.